#TITLE_ALTERNATIVE# - ROHMAN (NIM 12104084), ABDUL
Production rate in mine process is affected by work performance of haul trucks and excavators. Haul trucks interaction with ground will cause forces needed to drive the vehicle. The definition of rolling resistance is external forces that resist the vehicle to move. Coefficient of Rolling Resistance (CRR) is total rolling resistance divided by normal weight of the vehicle. This research's purpose is to estimate the rolling resistance and Coefficient of Rolling Resistance of vehicle move on sand gravel material, and analyze effect of tire to the road bearing capacity. CRR was measured by a simulation of a single lori that pulled by wire rope that operated by a winch machine with 13 m track. Variables that measured in this research are total vehicle weight (loaded), tire pressure, pulling velocity, and grade of the track. It is shown that the increase of payload weight, pulling velocity, and grade of the track can increase the number of CRR. But the increase of tire pressure will reduce the number of CRR. Dimensional analysis is conducted to determine the empirical relation between the number of CRR and those variables.